Cannon Residence Honor Awards Exhibition certificate - Southern California Chapter of the American Institute of Architects::::::::: (1963)
Honor Awards Exhibition certificate from the Southern California Chapter of the American Institute of Architects to William F. Cody informing him of the Cannon Residence's selection in the 1963 Honor Awards Exhibition by the International Panel of Judges.